Pripravljenost na interprofesionalno učenje pri študentih medicine, zdravstvenih ved in psihologije - Štukelj, Iva (Javno zdravje, 2019)
Interprofessional learning (this is when two or more people from different professions learn by working together) is ultimately supposed to lead to the best overall treatment of a patient. For this reason, our research examined the extent to which students of medicine, health sciences and psychology were prepared to do so. The sample included 110 students, aged between 20 and 25 years, 15 males and 91 females (others did not report their gender). Among them were 29 students of medicine, 48 students of psychology and 33 students of health sciences. The participants completed The Big Five Inventory (BFI), the Readiness for Interprofessional Learning Scale and the Teamwork Skills Questionnaire. The results have shown that students of medicine are less prepared for interprofessional learning than the other two groups of students. Individuals with previous experience in interprofessional learning scored higher on the Readiness for Interprofessional Learning Scale. A difference between genders has also been established, but we have to point out that only 15 males were included in the sample. The adjusted Readiness for Interprofessional Scale was shown to be a reliable measure, but it would be necessary to perform an additional validity check.
Keywords: course of study; gender; interprofesionalno učenje; interprofessional learning; osebnostne lastnosti; personality traits; spol; študijska smer; teamwork skills; timsko delo